The impact of the Russia-Ukraine war on the competitiveness of European airlines - Hašková, Simona; Šuleř, Petr; Divoká, Lenka (Business, Management and Economics Engineering, 2024)
Purpose – The research identifies the impact of the Russia-Ukraine war on the stock prices of six publicly traded European airlines and evaluates their ability to adapt to this situation. Research methodology – The dependence of the development of airline stock prices on the level of public and institutional stress due to the war was measured using GoogleTrends and is analysed on the basis of a Vector Autoregression model (VAR). Findings – A short-term negative relationship was confirmed between the development of stock prices and GoogleTrends; the impact of the stress related to the war was negligible about 5 months after the outbreak thereof. Those companies that were the fastest to adapt to the shock of the war in terms of share prices are identified. Research limitations – The link between GoogleTrends, as an input variable reflecting market sentiment, and the stock prices of European airlines, is considered a limitation. Practical implications – The impact of investor sentiment on the returns on the stocks of airlines is a thing of the past; which is an important finding for financial market participants and airlines alike. Originality/value – The ability of the specific airlines to adapt to the shock of war creates a competitive advantage.